ANALYSIS OF VEGETATION STRUCTURE IN THE MANGROVE ECOSYSTEM OF PENGARENGAN, PANGENAN, CIREBON REGENCY - Lutfianti Mutmainah, Annisa; Arief, Mochamad Candra Wirawan; Lewaru, Muhammad Wahyudin; Sunarto, Sunarto; Arifin, Intan Khairunissa; Yasmin, Putri Auliya (Universitas Mataram, 2025)
Mangrove ecosystems play an important role in maintaining coastal biological balance, protecting land from erosion, providing habitats for various biota, and functioning as effective carbon sinks. Indonesia has the largest mangrove area in the world, covering approximately 3.3 million hectares, but this ecosystem continues to experience degradation due to land conversion, with a rate of destruction reaching 530,000 hectares per year. This degradation reduces the ecological and economic functions of mangroves, necessitating vegetation structure analysis to assess the condition of the ecosystem. This study aims to analyze the vegetation structure of mangroves in Pengarengan Village, Pangenan District, Cirebon Regency, which is one of the oldest mangrove areas in Cirebon. Data collection was carried out at three stations using the Transect Line Plot method with plot sizes of 10×10 m² for trees, 5×5 m² for stakes, and 1×1 m² for seedlings. The parameters observed included density, frequency, and dominance, which were then used to calculate the Importance Value Index (IVI). The results showed that the mangrove vegetation at the study site was dominated by the species Rhizophora mucronata and Avicennia marina. The density of tree-level vegetation was classified as moderate to dense, with the highest density found at Station II (2,433 ind/ha) and the lowest density found at Station I (1,200 ind/ha). The INP value reached 300% for each species at all stations at the tree and stump levels, indicating the dominance of one species at each station